Systemic Therapy of Neuroendocrine Neoplasia: Single Center Experience from a Cohort of 110 Consecutive Cases - Karin Mayer; Selina Kiry; Anna Yordanova; Hojjat Ahmadzadehfar; Florian C. Gaertner; Ralph A. Bundschuh; Markus Essler; Maria A. Gonzalez-Carmona; Christian P. Strassburg; Hanno Matthaei; Philipp Lingohr; Savita Bisht; et al. (International Journal of Endocrinology)
Objective. Neuroendocrine neoplasias (NENs) represent a rare and biologically heterogeneous group of malignancies. Treatment of NEN patients remains challenging due to lack of prospective evidence on the choice of ideal therapeutic sequence and therapeutic efficacy in specific individual scenarios. Methods. Clinical data on 110 consecutive patients suffering from NEN treated at a single German university center were analyzed, therapeutic regimens applied were assessed, and the outcome was evaluated. Results. Histological grading, Ki67 proliferation index, functional activity, and presence of metastases were identified as prognostic markers. 10-year overall survival rates were 92%, 44%, and 0% for G1, G2, and G3 tumors, and 60%, 39%, 69%, 53%, and 0% for Ki67 <2%, 3–5%, 6–20%, 21–49%, and >50%, respectively. Peptide receptor radionuclide therapy (PRRT) and cytostatic chemotherapy were the second most common options, with PRRT being used more frequently in NET G1 and G2 and chemotherapy in NEC G3. Combination chemotherapy with etoposide plus cisplatin or carboplatin showed disease control rates (DCRs) of overall 74%, with a short median progression-free survival (PFS) of 7 or 5 months, respectively. DCR and PFS for PRRT were 89% and 22 months when administered as monotherapy, versus 100% and 27 months upon combination with somatostatin analog (SSA) therapy. Of note, PRRT also achieved disease control as best response in 5/5 (100%) selected cases of NEC G3. Conclusion. Further prospective studies are warranted to help stratify available options for therapeutic intervention in NEN patients.